The Effects Of Oral Communication Strategy Training And Metacognitive Awareness Strategy Training On Form Four Students’ Esl Speaking Performance In Selected Secondary Schools In Kedah - Singh, Tarsame Singh Masa (2013)
The purpose of this study was to investigate whether oral communication strategies and metacognitive awareness strategies for speaking would be effective in enhancing speaking performance, speech production rate, oral communication strategy use and level of metacognitive awareness strategies of Malaysian ESL secondary students. The sample of the study consisted of 199 students in 3 secondary schools in a northern state of Peninsula Malaysia. Students were formed into 3 intact groups. The first experimental group was taught speaking using CSMK based instructions method which comprise of oral communication strategy training (CS) and metacognitive awareness strategies for speaking. The second experimental group was taught speaking using the oral communication strategy training while the control group (T) did not undergo any special training apart from their regular teaching and learning process. The strategy based instructions (CSMK & CS) and regular method (T) are the independent variables, whereas speaking performance (SP), speech production rate (SPR), oral communication strategy use (OCSU) and metacognitive awareness strategy for speaking (MKA) are the dependent variables, the target of strategy based instructions. The data for this study was collected before and after the quasi-experiment through speaking test, corpus data based on the transcripts, oral communication strategy use questionnaire (OCSU), metacognitive awareness strategy for speaking checklist (MKA) and retrospective verbal protocol. The results show that CS group performed better than CSMK and T with reference to speaking performance, speech production rate, oral communication strategy use and metacognitive awareness strategy for speaking. The results are congruent with some related strategy-based training studies which suggest that oral communication strategies has a positive impact on enhancing ESL students speaking proficiency.